Performance Improvement of a Thin Film Thermoelectric Generator Optimisation of the Deposition Parameters - Nurfarhana Ahmad Musri; Yoganash Putthisigamany; Puvaneswaran Chelvanathan; Nadhrah Md Yatim; Farah Liana Mohd Redzuan; Ubaidah Syafiq (Royal Society of Chemistry (RSC), 2026)
Tier 2 (Indexed by WOS/Scopus/ERA)